KIDNEY FUNCTION DISORDERS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND OBESITY: DIAGNOSTIC AND THERAPEUTIC PERSPECTIVES - Akhmedova Lola Abdulkhamidovna (Journal of Applied Science and Social Science, 2026)
Chronic obstructive pulmonary disease (COPD) and obesity are common chronic conditions that frequently coexist and contribute to multisystem dysfunction. Among the less frequently discussed but clinically significant complications in such patients are kidney function disorders. The interaction between chronic hypoxia, systemic inflammation, oxidative stress, hemodynamic instability, insulin resistance, and metabolic abnormalities may accelerate renal impairment in this population. This article examines the mechanisms underlying kidney dysfunction in patients with COPD and obesity, highlights the main diagnostic approaches, and discusses current therapeutic perspectives. Early recognition of renal impairment in these patients is essential for improving prognosis, reducing complications, and optimizing multidisciplinary care.